'Prove it' Working with LBGTQ+ Asylum Seekers who Must Prove their Sexuality to Stay in the UK. Issue 3 (November 2018) - Ward, Jason
As Great Britain reaches 50 years of LBGTQ+ legislation, making it illegal to persecute an individual based on their sexual identity, not everywhere in the world is so enlightened. In some parts of the world, the act of homosexuality is punishable by law, with people sentenced to incarceration or even death. For some people, trying to leave their country and claim asylum in another part of the world is the only way people can truly be themselves. This paper is based on the case studies of two male clients who are both waiting for an asylum decision, with both cases based on their sexuality, and the approach used in therapy sessions, specifically focusing on not only coming to terms with their own persecution, moving from shame of their own culture, but also working with frustration and the re-shaming effects of proving one's sexuality. The overall objective is to create an argument for Dramatherapy when working with complex trauma, shame and raising awareness of the lesser-known work of Dramatherapy and asylum seekers.